Dating acts in its Jewish and Greco-Roman contexts - Armstrong, Karl L. (Library of New Testament studies, 2020)
Acknowledgements -- List of Tables -- List of Abbreviations Chapter 1: A New Plea for an Early Date Of Acts -- Chapter 2: A Historiographical Approach to the Date Of Acts Chapter 3: The Date of Acts and its Sources Chapter 4: The Sources of Acts: Paul's Letters and the Works of Josephus Chapter 5: The Un-Enigmatic End of Acts Chapter 6: The End of Acts and the Jewish Response Chapter 7: The End of Acts and the Comparable Age of its Variants Chapter 8: Acts in its Jewish and Greco-Roman Historical Context Chapter 9: Conclusion Appendix: The Manuscript Record for Acts 28:11?31 Bibliography